Effects of a classroom discourse intervention on teachers' practice and students' motivation to learn mathematics and science. (February 2015) - Kiemer, Katharina; Gröschner, Alexander; Pehmer, Ann-Kathrin; Seidel, Tina
Abstract: Student interest and motivation in STEM subjects has dropped significantly throughout secondary education, for which teacher–student interactions are named as a central reason. This study investigated whether a video-based teacher professional development (TPD) intervention on productive classroom discourse improved students' learning motivation and interest development over the course of a school year. The teachers' intervention group (IG; n = 6) was compared with a control group (CG; n = 4) who participated in a traditional TPD programme on classroom discourse. The teachers showed a significant increase in constructive feedback and decrease in simple feedback as a function of the treatment. Pre- and post-tests revealed that students in the IG ( n = 136) significantly increased their perceived autonomy, competence and intrinsic learning motivation as compared with those in the CG ( n = 90). They also showed significantly greater interest changes in the subjects compared with their peers in the CG. Highlights: TPD on productive classroom discourse has positive effects on students' interest. Reflection-based TPD promotes productive teacher discourse practices. Changes in students' situational motivation predict changes in interest during TPD.